Topical Curcumin-Based Cream Is Equivalent to Dietary Curcumin in a Skin Cancer Model - Kunal Sonavane; Jeffrey Phillips; Oleksandr Ekshyyan; Tara Moore-Medlin; Jennifer Roberts Gill; Xiaohua Rong; Raghunatha Reddy Lakshmaiah; Fleurette Abreo; Douglas Boudreaux; John L. Clifford; Cherie-Ann O. Nathan (Journal of Skin Cancer)
Skin squamous cell carcinoma (SCC), the most common cancer in the USA, is a growing problem with the use of tanning booths causing sun-damaged skin. Antiproliferative effects of curcumin were demonstrated in an aggressive skin cancer cell line SRB12-p9 (P<0.05 compared to control). Topical formulation was as effective as oral curcumin at suppressing tumor growth in a mouse skin cancer model. Curcumin at 15 mg administered by oral, topical, or combined formulation significantly reduced tumor growth compared to control (P=0.004). Inhibition of pAKT, pS6, p-4EBP1, pSTAT3, and pERK1/2 was noted in SRB12-p9 cells post-curcumin treatment compared to control (P<0.05). Inhibition of pSTAT3 and pERK1/2 was also noted in curcumin-treated groups in vivo. IHC analysis revealed human tumor specimens that expressed significantly more activated pERK (P=0.006) and pS6 (P<0.0001) than normal skin samples. This is the first study to compare topical curcumin to oral curcumin. Our data supports the use of curcumin as a chemopreventive for skin SCC where condemned skin is a significant problem. Prevention strategies offer the best hope of future health care costs in a disease that is increasing in incidence due to increased sun exposure.